2015
DOI: 10.1016/j.jcrs.2014.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after monocular corneal inlay implantation for the surgical compensation of presbyopia

Abstract: Dr. Grabner was reimbursed for travel expenses from Acufocus. Dr. Riha is a consultant to Acufocus. No other author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 16 publications
4
57
1
Order By: Relevance
“…Patient satisfaction after KAMRA inlay has been evaluated by several studies and has been shown to be good 7,9,11,17. Patient satisfaction from the FDA clinical trials was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Patient satisfaction after KAMRA inlay has been evaluated by several studies and has been shown to be good 7,9,11,17. Patient satisfaction from the FDA clinical trials was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…19,26 The explantation rate in cases of visual dissatisfaction varies widely across series from 0% to 21%. 14,22,[27][28][29] One study concluded that after removal, corneal topography and aberrometry were not permanently affected with a return to preoperative corrected and uncorrected vision in the majority of cases. 30 Advances in the biocompatibility of materials and designs allowing for improved metabolic regulation have made modern inlays much safer than their precursors.…”
Section: ' Postoperative Complicationsmentioning
confidence: 99%
“…36 Even 6 months after initial placement, successful recentration has been reported. 19,26,29 Epithelial ingrowth can rarely occur after corneal inlay placement. Authors have described the successful treatment of ingrowth by lifting the flap, meticulous removal of the ingrowth, and placement a nylon suture at flap margin, similar to the treatment of ingrowth after LASIK.…”
Section: ' Postoperative Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the postoperative distance visual acuity is not influenced by the pupil size [12] of the patient after KAMRA inlay implantation. There are also long-term studies [13][14][15] that show a significant increase of visual acuity in intermediate and near vision [16], but with a slight decrease in distance vision, in the eye that the inlay is implanted. However, binocular distance vision and stereopsis do not seem to be affected by the procedure [16].…”
Section: Introductionmentioning
confidence: 99%